ANALISIS PENUMPANG KAPAL TITANIC MENGGUNAKAN TITANIC DATASET DENGAN BANTUAN PEMROGRAMAN PYTHON - Alfian Fakhri; Yekti Condro Winursito (JOURNAL SAINS STUDENT RESEARCH, 2024)
Titanic was a popular luxury passenger ship and sank on April 15, 1912. The Titanic accident was one of the most tragic events. As a result, the Titanic continues to be an object of study, research and discussion by various groups. One of the results of research into the sinking of the Titanic is a sample dataset of Titanic passengers. The primary goal of this research is to uncover insights, patterns, and relationships in the data set to better understand the factors that determined the survival of Titanic passengers. The research method used uses a quantitative approach. The quantitative analysis method focuses more on proving something through mathematical and statistical analysis. Data collection is carried out by taking data from the Titanic dataset. The results of this research are that the majority of passengers are in their twenties, with the highest concentration of passengers being in that age group. Unfortunately, more passengers did not survive the tragedy, with the proportion of male passengers who did not survive being greater than female passengers. There is a clear correlation between ticket class and passenger survival rate.